Unlocking the potential of microbotox compared with fractional carbon dioxide laser in the treatment of postacne scars: a comparative split-face study - Walid Medhat; Noha Moftah; Ahmed F. Rezk (Journal of the Egyptian Women’s Dermatologic Society)
Background Several research studies have examined the impact of fractional carbon dioxide (CO2) laser (FCL), but only a limited number have investigated the effects of microbotox injections as a treatment for postacne scars. Yet, no evaluation has been performed to compare the results of these two methods. Objective To assess and make a comparison between the safety and effectiveness of Microbotox injections and FCL in the treatment of postacne scars. Patients and methods One facial side was assigned randomly to undergo FCL once every month for three months, while the opposite side was subjected to a single session of Microbotox injection. Two dermatologists, unaware of the treatment details, assessed the clinical enhancements. Additionally, Goodman’s acne scar score together with patients’ satisfaction were assessed at the end of the study. Results The study involved 26 participants, with 12 (46%) males and 14 (54%) females, whose ages ranged from 18 to 27 years (with an average of 28.12±5.4). Notably, both FCL and Microbotox treatments resulted in a significant decrease in the Goodman global score (P=0.03 and P<0.0001, respectively). However, Microbotox exhibited superior outcomes (P=0.027). Additionally, there was a statistically significant distinction between the outcomes and patient contentment for both treated sides (P<0.001). The study did not encounter any major adverse effects, apart from mild discomfort, temporary redness, and a few cases of postinflammatory hyperpigmentation. Conclusion Both FCL and Microbotox expressed significant improvement in acne scars. However, Microbotox revealed a significantly better, and faster, yet short-lived effect.